2013
DOI: 10.1007/978-3-642-40498-6_66
|View full text |Cite
|
Sign up to set email alerts
|

Using Graphical Representations to Support the Calculation of Infusion Parameters

Abstract: Abstract.A variety of medical procedures require arithmetic calculations to be performed. These calculations can be complex and induce errors that can have serious consequences on the ward. In this paper, we consider whether a graphical representation might make these calculations easier. The results of a laboratory experiment are reported in which participants were asked to solve a number of infusion parameter problems that were represented either graphically or textually. Results show that participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The finding that a graphical representation can improve some aspect of number entry is consistent with previous work (Gould et al, 2013;Thimbleby & Williams, 2013). However, these studies focused on a calculation task and the representations were designed to show the relation between multiple numbers.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The finding that a graphical representation can improve some aspect of number entry is consistent with previous work (Gould et al, 2013;Thimbleby & Williams, 2013). However, these studies focused on a calculation task and the representations were designed to show the relation between multiple numbers.…”
Section: Discussionsupporting
confidence: 83%
“…If the values of two parameters are known, a line can be drawn through these two points on the scales which then intersects with the third scale at a point corresponding to the correct value for that parameter. Gould et al (2013) developed a graphical representation to help people visualize the rate of infusion in an infusion pump programming task. In the graphical representation, shown in Figure 1b, the rate of infusion can be inferred from the gradient of the line (connecting duration of infusion and volume to be infused).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that these representations can significantly reduce the number of errors made in medical dosage calculation tasks. Inspired by Thimbleby's work, Gould et al (2013) proposed a variation of GRs to make it easier for users to reason about the setup of infusions. The purpose of using a bar graph with a scale ruler Number-based Graphical Representations for Error Detection 199 is not the same as using GRs in our design.…”
Section: Graphical Representationsmentioning
confidence: 99%
“…In this study, we propose a method of using number-based graphical representations (GRs) to help users identify entry errors. The use of GRs plays an important role in many areas such as data analysis (Larkin and Simon, 1987) and clinical setting (Gould et al, 2013;Thimbleby and Williams, 2013). To display numbers graphically, we designed a mechanism that constructs a GR corresponding to a number; each number thus 196 Huawei Tu et al having a unique GR.…”
Section: Introductionmentioning
confidence: 99%